Significance of Umbilical Artery Velocimetry in Perinatal Outcome of Growth Restricted Fetuses (Journal of Bangladesh College of Physicians and Surgeons, 2016)
Objectives: To study pregnancy outcomes in growth restricted fetuses with normal umbilical artery velocimetry, low end-diastolic umbilical flow, and absent or reversed diastolic flow. Methods: Fifty pregnant women with growth restricted fetuses were evaluated by umbilical artery velocimetry between 28 and 39 weeks of pregnancy. Outcome of pregnancy was recorded for the normal Doppler group (n=17; 34%), the low end diastolic flow group (n=23; 46%), the group with absent diastolic flow (n=8; 16%) and the group with reversed diastolic flow (n=2; 4%). Results: The average birth weight, diagnosis to delivery interval and gestational age at delivery were comparatively lower in case of abnormal umbilical Doppler velocimetry group. Again there was higher incidence of LSCS for fetal distress, Apgar score